ERRORS IN LONG VOWEL PRONUNCIATION: A CASE OF ENGLISH LANGUAGE EDUCATION DEPARTMENT STUDENTS - Rosalin Ismayoeng Gusdian (Widya Mandala Surabaya Catholic University, 2021)
The study aims to investigate the errors in the long vowel realizations committed by students of English Language Education Department. It is a case study of the English Language Education Department students of Universitas Muhammadiyah Malang. The study employed qualitative method. The data were the recorded pronunciation of twenty students from the Speaking for Informal Interaction class at Universitas Muhammadiyah Malang. The data were collected when the students performed a storytelling for three to five minutes. In the data analysis, all of the recordings were carefully listened and the mispronunciation of words containing the targeted long vowels was identified. Upon the long vowel error identification, the students’ long vowel production was phonologically transcribed and assigned into the table of long vowels. The table was set according to the classification of the five types of English long vowels, namely [ɑ:], [ɛ:], [i:], [ɔ:], [u:]. Further, the phonological transcription analysis referred to Received Pronunciation (RP) and General American (GA) as the accepted pronunciation standards. The result shows that the English long vowels [i:], [ɑ:], [ɛ:], [u:], and [ɔ:] are replaced with the short vowels [ʌ], [i], [ɛ], [u], and [ɔ] respectively. The replacement is implemented due to the absence of the targeted sounds in the students native language (Bahasa). This phenomenon is the result of phonological transfer.